Fixed-dose combination of AR-13324 and latanoprost: a double-masked, 28-day, randomised, controlled study in patients with open-angle glaucoma or ocular hypertension. Issue 3 (24th July 2015) - Lewis, Richard A; Levy, Brian; Ramirez, Nancy; C Kopczynski, Casey; Usner, Dale W; Novack, Gary D; ,
Abstract : Background/aims: To evaluate the ocular hypotensive efficacy of fixed-dose combinations of the Rho kinase inhibitor and norepinephrine transport inhibitor AR-13324 (0.01% and 0.02%) and latanoprost (PG324 Ophthalmic Solution) relative to the active components AR-13324 0.02% and latanoprost 0.005%, used bilaterally at night. Methods: This was a double-masked, randomised, parallel comparison study in patients with open-angle glaucoma or ocular hypertension. After washout, patients were randomised to one of four treatment arms and treated for 28 days. The primary efficacy variable was mean diurnal intraocular pressure (IOP) at day 29. Results: We randomised 298 patients, of whom 292 (98%) completed the study. Mean unmedicated diurnal IOPs (study eye) was 25.1, 25.1, 26.0 and 25.4 in the PG324 0.01%, PG324 0.02%, latanoprost and AR-13324 0.02% groups, respectively. On day 29, mean diurnal IOP decreased to 17.3, 16.5, 18.4 and 19.1 mm Hg, respectively. For the primary efficacy variable of mean diurnal IOP at day 29, PG324 0.02% met the criterion for statistical superiority relative to both latanoprost and AR-13324 0.02% (p<0.0001), providing additional IOP lowering of 1.9 and 2.6 mm Hg, respectively. PG324 0.01% also met the criterion for superiority. The most frequently reported adverse event was conjunctival hyperaemia with an incidence of 41% (30/73), 40% (29/73), 14% (10/73) and 40% (31/78) in the PG324 0.01%, PG324 0.02%, latanoprost and AR-13324 0.02% groups, respectively. Conclusions: In this short-term study, the fixed-dose combination of AR-13324 0.02% and latanoprost 0.005% in PG324 Ophthalmic Solution provides clinically and statistically superior ocular hypotensive efficacy relative to its individual active components at the same concentrations. The only safety finding of note was transient asymptomatic conjunctival hyperaemia which was typically of mild severity. Trial registration number: NCT02207491.